2004
DOI: 10.1038/sj.cdd.4401457
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipin and its metabolites move from mitochondria to other cellular membranes during death receptor-mediated apoptosis

Abstract: We previously reported that during death receptor-mediated apoptosis, cardiolipin (CL) relocates to the cell surface, where it reacts with autoantibodies from antiphospholipid syndrome sera. Here, we analysed the intracellular distribution of CL and its metabolites during the early phase of cell death signalling triggered by Fas stimulation in U937 cells and mouse liver. We found a redistribution of mitochondrial CL to the cell surface by using confocal microscopy and flow cytometry. Mass spectrometry revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
132
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(141 citation statements)
references
References 64 publications
7
132
0
2
Order By: Relevance
“…Two different mechanisms are believed to be used by the cell to ensure mitochondrial homeostasis and survival; apoptosis and mitophagy but, to the best of our knowledge, none of these has been considered in the context of thermal acclimation. Of interest, both processes are potently regulated by cardiolipin and its function to anchor cytochrome c to the inner mitochondrial membrane, and have been shown to be triggered by cardiolipin modifications (Bradley et al, 2016;Chu et al, 2013;Sorice et al, 2004). The release of cytochrome c triggers apoptosis and cell death (Goldstein et al, 2000), and it is therefore possible that the increased cytochrome c effect we observed upon warming induced this mechanism.…”
Section: Discussionmentioning
confidence: 87%
“…Two different mechanisms are believed to be used by the cell to ensure mitochondrial homeostasis and survival; apoptosis and mitophagy but, to the best of our knowledge, none of these has been considered in the context of thermal acclimation. Of interest, both processes are potently regulated by cardiolipin and its function to anchor cytochrome c to the inner mitochondrial membrane, and have been shown to be triggered by cardiolipin modifications (Bradley et al, 2016;Chu et al, 2013;Sorice et al, 2004). The release of cytochrome c triggers apoptosis and cell death (Goldstein et al, 2000), and it is therefore possible that the increased cytochrome c effect we observed upon warming induced this mechanism.…”
Section: Discussionmentioning
confidence: 87%
“…A few PE (three lipids), PI (three lipids), PS (two lipids), and a PA (one lipid) were also observed. Acyl-PG are unusual lipids commonly found in bacterial cells, which have been reported to accumulate in mitochrondrial fractions of mammalian apoptotic cells (31), and to be present at significant levels in Golgi membranes (32). PG lipids are present at low levels (1-2%) in most animal tissue and can serve as the precursor of CL found in mitochrondrial membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid extraction from purified mitochondria was accomplished as described earlier and extracts were analyzed by nanoelectrospray time of flight mass spectrometry using an LCT instrument (Micromass, Elstree, UK) set in positive ion mode. 33 A few microliters of the extracts were injected using capillary voltage at 2250 V and sample cone at 35 V. Semi-quantitative evaluation of lipid peaks was undertaken using a set of internal reference ions that maintained equivalent relationships within multiple spectra of the same sample and showed little variation between WT and HtrA2 KO samples. The data were normalized to the major phosphatidyl choline, that is PO-PC (mass-tocharge ratio m/z 758), which was in turn normalized to other reference ions such as C-24 ceramide (m/z 685).…”
Section: Methodsmentioning
confidence: 99%